Theoretical analysis and modeling of photoemission characteristics of GaAs nanowire array photocathodes. (11th September 2015) - Ge, Xiaowan; Zou, Jijun; Deng, Wenjuan; Peng, Xincun; Wang, Weilu; Jiang, Shaotao; Ding, Xiaojun; Chen, Zhaoping; Zhang, Yijun; Chang, Benkang
Abstract: Gallium arsenide (GaAs) nanowire array (NWA) photocathodes have unique electrical and optical properties. Based on studies about photon absorption, band structure, and electron transport properties of GaAs nanowire, a photoemission model for GaAs NWA photocathodes is established. According to the model, we simulate and analyze the photocurrent, spectral response, and absorption properties of ordered GaAs NWA photocathodes. The results present a very interesting phenomenon; the photocurrent and spectral response peak at incident angles of 20° and 30°, respectively. These special properties of NWA cathodes differentiate them from their thin film counterparts. We also analyze the effects of nanowire length and diameter on the photocurrent of NWA cathodes, and find the optimum height of the nanowires is 10 μ m. This study shows that NWAs exhibit higher absorbance and excellent charge transport. Thus, GaAs NWA photocathodes are excellent candidates for electron sources.